2000
DOI: 10.1007/bf02439809
|View full text |Cite
|
Sign up to set email alerts
|

Effect of semisynthetic analog of α1-acid glycoprotein on immunomodulatory and antiinflammatory activity of natural glycoproteinglycoprotein on immunomodulatory and antiinflammatory activity of natural glycoprotein

Abstract: Pseudo-alpha(1)-acid glycoprotein with carbohydrate chain ratio typical of native form was synthesized by a previously developed original technique of quantitative transfer of alpha(1)-acid glycoprotein carbohydrate chains to other polymeric carrier. Similarly to native glycoprotein, the semisynthetic analog inhibited lymphocyte proliferation and stimulated the production of antiinflammatory cytokines by peripheral blood mononuclear leukocytes. However, it possessed no antioxidant activity and did not inhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…Pukhal'skii et al reported that human AGP inhibits neutrophil superoxide anion generation and suggested that the antioxidant activity of AGP is due to the binding of free radicals, rather than to the inhibition of neutrophil activation. 13) The data obtained here support this proposal. Based on this mechanism, it is possible that AGP prevents the oxidation of DRD to RD from H 2 O 2 ( Table 2).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Pukhal'skii et al reported that human AGP inhibits neutrophil superoxide anion generation and suggested that the antioxidant activity of AGP is due to the binding of free radicals, rather than to the inhibition of neutrophil activation. 13) The data obtained here support this proposal. Based on this mechanism, it is possible that AGP prevents the oxidation of DRD to RD from H 2 O 2 ( Table 2).…”
Section: Discussionsupporting
confidence: 82%
“…We also investigated the effects of AGP on the oxidative changes in erythrocytes exposed to oxygen radicals, because AGP has been reported to inhibit neutrophil aggregation and superoxide anion generation induced by formyl-methionyl-leucyl-phenylalanine, phorbol myristate acetate 12) and phytohemagglutinin. 13) These studies were carried out using AGP and desialylated AGP to determine the role of sialic acid in this process.…”
mentioning
confidence: 99%
“…40) However, fMLP might activate protein kinase C (PKC) receptors existed in neutrophils but PMA might directly activate for PKC. PKC phosphorylates and activates NADPH oxidase, resulting in the generation of superoxide anion.…”
Section: Discussionmentioning
confidence: 99%
“…The cytokines, in turn, modulate T-cell proliferation and function (29,58). Because of the immunomodulatory potential associated with the carbohydrates of the AAG glycoforms, these molecules, or pseudo-glycoproteins mimicking their activity, represent molecules with pharmacological potential for modulation or prevention of atherogenesis-promoting processes (51,58).…”
Section: Discussionmentioning
confidence: 99%